The behaviour of Cu in copper removal from carbon saturated molten iron by FeS-based decopperization agents. (21st April 2022) - Lu, Zhihao; Liu, Chengjun
ABSTRACT: The mechanism of removal of Cu from carbon saturated iron with FeS-based agents is investigated at 1350°C. The Na2 S in the FeS-based agents plays an important role, including fixing FeS, limiting its dissolution into molten iron, and absorbing fixed products during decopperization treatment. The optimal copper removal rate in 15 min is 95.1% when the Na2 S-FeS slag with XFeS /XNa2S  = 6/4 is used, and the sulphur content can be controlled at about 0.032 wt-% when the Na2 S-FeS slag with XFeS /XNa2S  = 2/8 is used. Then the copper removal mechanism of FeS-based decopperization agents in carbon saturated molten iron is studied by investigating the non-metallic inclusions in the process samples and crucible samples collected in the experiments using different agents. And the detection and analysis methods ICP-AES, SEM-EDS, XRD are used.